2014
DOI: 10.1111/cen.12399
|View full text |Cite
|
Sign up to set email alerts
|

Maternal thyroid hormones during pregnancy, childhood adiposity and cardiovascular risk factors: the Generation R Study

Abstract: Maternal thyroid function during early pregnancy may influence childhood body composition and cardiovascular development. Further studies are needed to replicate these findings and to examine the influence of maternal thyroid hormone levels during pregnancy on long-term growth and cardiovascular development in the offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…Only one study has previously investigated the association between maternal thyroid dysfunction and offspring cardiometabolic risk factors (26). In this study, no association was found with either subclinical or overt maternal thyroid disease.…”
mentioning
confidence: 57%
“…Only one study has previously investigated the association between maternal thyroid dysfunction and offspring cardiometabolic risk factors (26). In this study, no association was found with either subclinical or overt maternal thyroid disease.…”
mentioning
confidence: 57%
“…Recent studies in experimental animals (30) and in humans (31,32,33) have considered thyroid hormone abnormalities as the exposure and cardiovascular function as the outcome. A study in rats (30) suggested that maternal thyroid hormone levels are important in the development of hypothalamic neurons regulating cardiovascular functions.…”
Section: Hypothesis Of Fetal Programing By Maternal Thyroid Dysfunctionmentioning
confidence: 99%
“…However, how alterations in maternal and foetal TH levels may affect child development is an important area of study. Data from the Generation R study reveal that maternal thyroid levels during pregnancy may influence childhood adiposity and potentially cardiovascular development . Lower maternal TSH levels and higher maternal fT4 levels were associated with lower childhood BMI.…”
Section: Introductionmentioning
confidence: 99%